Safety of Using Direct Oral Anticoagulants in Patients with Atrial Fibrillation and Chronic Kidney Disease - V. I. Petrov; O. V. Shatalova; A. S. Gerasimenko; V. S. Gorbatenko (Рациональная фармакотерапия в кардиологии)
The purpose of this review is to examine the possibilities and prospects for the use of direct oral anticoagulants for the prevention of thromboembolic complications in patients with atrial fibrillation and chronic kidney disease. Chronic kidney disease is an independent risk factor for cardiovascular complications. Atrial fibrillation is associated with a higher risk of developing chronic kidney disease and more rapid progression of existing renal pathology. The presence of chronic kidney disease in atrial fibrillation on the one hand leads to an increased risk of thromboembolism, and on the other to an increased risk of bleeding when using anticoagulants. The standard for the prevention of thromboembolic complications in atrial fibrillation, including those with concomitant renal pathology, was considered warfarin for many years. However, modern studies have shown that the use of warfarin may enhance vascular calcification in patients with chronic kidney disease, which in turn may lead to an increased risk of ischemic strokes.Analyzing clinical recommendations, randomized studies, meta-analyzes and a systematic review on the use of anticoagulants in patients with atrial fibrillation and renal pathology, revealed the advantage of using direct oral anticoagulants over warfarin at stage 1-3 of chronic kidney disease. Data on the use of direct oral anticoagulants with a more pronounced renal dysfunction and in patients on dialysis is limited due to the lack of a sufficient number of large randomized studies. Due to the presence of renal clearance in all oral anticoagulants, their pharmacokinetics changes to some extent with a decrease in the glomerular filtration rate, which requires dose adjustment of drugs depending on creatinine clearance. Therefore, the use of anticoagulants for the prevention of thromboembolic complications during atrial fibrillation requires special attention in patients with chronic kidney disease.